2020
DOI: 10.1007/s10928-020-09682-4
|View full text |Cite
|
Sign up to set email alerts
|

Assessing parameter uncertainty in small-n pharmacometric analyses: value of the log-likelihood profiling-based sampling importance resampling (LLP-SIR) technique

Abstract: Assessing parameter uncertainty is a crucial step in pharmacometric workflows. Small datasets with ten or fewer subjects appear regularly in drug development and therapeutic use, but it is unclear which method to assess parameter uncertainty is preferable in such situations. The aim of this study was to (i) systematically evaluate the performance of standard error (SE), bootstrap (BS), log-likelihood profiling (LLP), Bayesian approaches (BAY) and sampling importance resampling (SIR) to assess parameter uncerta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 15 publications
(28 reference statements)
1
18
0
Order By: Relevance
“…Although the bootstrap is often branded as an approach gain a good understanding of the uncertainty in small samples, Broeker and Wicha have shown that this is mostly wishful thinking as the performance in small datasets is not good [24]. We confirm this here in the two scenarios S Hill,smallR and S Hill,smallS .…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Although the bootstrap is often branded as an approach gain a good understanding of the uncertainty in small samples, Broeker and Wicha have shown that this is mostly wishful thinking as the performance in small datasets is not good [24]. We confirm this here in the two scenarios S Hill,smallR and S Hill,smallS .…”
Section: Discussionsupporting
confidence: 77%
“…With even lower number of subjects, especially in the sparse design, the bias on the parameter estimates for the asymptotic method was even more apparent (data not shown) and the bootstrap approaches could not recover from these poor estimates. With these scenarios the coverage for all bootstraps was lower than 90%, and there was no clear trend in whether the bootstraps under-or over-estimated the parameters and their SE, which is a cautionary message for the usage of bootstrap in practice as from present and previous work [15,24] the conditions in which bootstrap performances are adequate are not obvious. In our simulations, we found that the performance of the bootstraps degrade as the informativeness of the design decrease.…”
Section: Discussionmentioning
confidence: 74%
“…However, the concurrent use of various models will include a larger range of covariates. Third, single models developed in small, homogenous cohorts of patients while displaying good internal predictivity, might not display external predictivity due to selection bias in the covariate submodel 35 and underestimated parameter uncertainty in studies with small patient numbers 36 . Finally, single models may have been developed based upon routine clinical data, which often exhibits uncertainty in documented dosing and sampling time.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical data examples, models were evaluated by graphical and numerical criteria (goodness of fit plots, visual predictive checks and drop in objective function value (dOFV)). The LLP-SIR (log-likelihood-profiling based sampling-importance-resampling) method was employed for the assessment of parameter uncertainty, since a small number of subjects or cases was investigated [17].…”
Section: Population Pharmacokinetic Modellingmentioning
confidence: 99%